2005
DOI: 10.1165/rcmb.2003-0435oc
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 or 2 Agonists Decrease Allergic Inflammation

Abstract: Toll-like receptors (TLRs) recognize highly conserved microbial molecular patterns, such as found in endotoxin. This study tested whether TLR4 and TLR2 stimulation in vivo would modulate subsequent adaptive (allergic) immune responses. We analyzed the effects of pulmonary administration of a TLR4 agonist, lipid A (LpA), and two TLR2 agonists, peptidoglycan (Ppg) and PamCys, in a murine model of allergic inflammation. The TLR agonists were administered during allergen sensitization or challenge. Both TLR agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 38 publications
3
93
2
2
Order By: Relevance
“…Intratracheally administered PGN (75 μg) also primarily induces IL-13 secretion in BAL from adult BALB/c mice (Schaub et al, 2004). Our results may differ from those of Velasco et al (2005), possibly because of the different route of administration, PGN dose, strain and age of animals and measurement parameters used.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Intratracheally administered PGN (75 μg) also primarily induces IL-13 secretion in BAL from adult BALB/c mice (Schaub et al, 2004). Our results may differ from those of Velasco et al (2005), possibly because of the different route of administration, PGN dose, strain and age of animals and measurement parameters used.…”
Section: Discussioncontrasting
confidence: 52%
“…TLR ligands such as PGN, LPS and CpG-ODN, modulate the immune response via TLR-2, -4 and -9 mediated pathways, respectively, particularly in the direction of Th1 dominance (Eisenbarth et al, 2002;Vollmer et al, 2004;Velasco et al, 2005). It has been reported that intratracheal instillation of PGN (225 μg) 13, a Th2-type cytokine, in the BAL from OVA-stimulated adult C57BL/6 mice (Velasco et al, 2005). Intratracheally administered PGN (75 μg) also primarily induces IL-13 secretion in BAL from adult BALB/c mice (Schaub et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, upregulation of TLR2-expression has been shown in farm children at school age 4 , and TLR2/TLR4-upregulation was strongly determined by maternal exposure to stables during pregnancy 3 . These human data were supported by murine studies, demonstrating decreased allergic responses following TLR2/TLR4 stimulation 5 .…”
Section: Introductionmentioning
confidence: 68%
“…We provide evidence that cystatin protects from inflammation in a systemic fashion, as reflected by its effects on remarkably different compartments, such as the lung and the gut. Moreover, the protein inhibits Th2-related as well as macrophage-related inflammation, which stands in stark contrast to the effect of TLR2 and TLR4 agonists of bacterial origin that have recently been shown to downregulate Th2-driven allergic responses in mouse models (56,57). These components act through stimulation of Th1 responses, as evidenced by elevated production of IFN-␥ and other Th1 cytokines, which is clearly not the case for filarial cystatin.…”
Section: Discussionmentioning
confidence: 88%